El acervo histórico antártico: estudio y preservación de restos testimoniales - Montalbán, Cristina (Centro de estudios hemisféricos y polares, 2010)
This study is about the rest of a shipwreck located nearby the Base Cientifica Antartica Artigas. From 1995 to 2003, some of that shipwreck pieces has been studied by different professionals whose reports have helped to determine the main characteristics of the archaeological deposit. At the same time, the analysis of the samples has allowed the possibility of handling several theories of the identification of the ships belonging. With the necessary interaction, from the historic point of view, we instrument the theoretical sustain, the rescue of the memory of the archaeological rests. In the process of building a historic background, we followed an investigation plan based on some basic guidelines. 1) We determined the antecedents, motivations and times in which the area was recorded in historical reports. 2) We plotted the actions in their geographical background (in the matter that concerns us- by the navigators, particularly by the seals ships). 3) We make a list of all the shipwrecks occurred in that zone. As a conclusion, it is our belief that it is necessary to alert future generations about the farther signification of the archaeological remains available in the Antarctic territory, and the need to create a cadastre of the Antarctic Archaeological Heritage that evidently has to be historically endorsed. Este estudio trata de los restos de un naufragio localizados en proximidades de la Base Científica Antártica Artigas. Desde 1995 a 2003 el pecio fue estudiado por distintos profesionales, cuyos informes han servido de base para determinar las principales características del yacimiento. Paralelamente, el análisis de las muestras, ha posibilitado el manejo de teorías de identificación de la embarcación a la cual podían pertenecer. En la interacción necesaria, desde el punto de vista histórico, instrumentamos el sustento teórico, el rescate de la memoria de los restos arqueológicos. En el proceso de armar un marco histórico, cumplimos un plan de investigación asentado en fundamentos básicos: 1) ...